Efficacy, safety and pharmacokinetics of tenofovir disoproxil fumarate in virologic-suppressed HIV-infected children using weight-band dosing - Linda Aurpibul (2018)
© 2015 Wolters Kluwer Health, Inc. Background: Tenofovir disoproxil fumarate (TDF) is approved for children but concerns remain about long-term renal and bone toxicity. We evaluated the efficacy, safety and pharmacokinetics of TDF in treatment-experienced children during 96 weeks. Methods: This was a prospective, open-label study in HIV-infected children 3-18 years of age (≥15 kg), with viral suppression on their first-line regimen without tenofovir. Children were given TDF/lamivudine/efavirenz once daily at entry; TDF was prescribed according to weight bands. Age-, gender- and CD4-matched controls receiving TDF-sparing regimens were concomitantly enrolled. Tenofovir pharmacokinetic assessment was performed at week 4. CD4 counts, HIV-1 RNA viral load and safety assessments were determined at baseline, 24, 48 and 96 weeks. Results: Eighty children were enrolled (40 per group); 35 (44%) were male. Median age was 12.2 (range 3.1-17.7) years. The median administered dose was 214 mg/m2. Tenofovir geometric mean AUC0-24 hours, Cmaxand C24 hourswere 2.66 [90% confidence interval (CI) 2.49-2.84] μg hours/mL, 0.26 (0.24-0.29) μg/mL and 0.057 (0.052-0.062) μg/mL, respectively. Estimated glomerular filtration rate did not significantly change overtime. The fractional excretion of calcium slightly increased but fractional excretion of phosphate was unchanged among children in TDF group. The bone mineral density Z score decreased in the first 24 weeks of TDF treatment and was stable afterward. The TDF group had lower cholesterol levels (P = 0.001). Thirty-nine of 40 children remained virologically suppressed. No serious adverse event related to tenofovir. Conclusion: TDF substitution in children and adolescents who were otherwise stable while receiving a first-line nonnucleoside reverse transcriptase inhibitor-based regimen achieved adequate exposure without clinically significant renal or bone adverse events over 96 weeks. While reassuring, these preliminary safety findings may not exclude delayed effects on renal function and bone density.